Tuberculosis and pregnancy - Ludmir, A. (2015)
We have presented the experience gained in the San Bartolome Hospital, as regards Tuberculosis and gestation between 1962 - 1964. It has also adopted the system for the oversight. Of a total of 5,127 pregnant women, we have had an incidence of 2.5%. Anamnesis data or no clinical findings, so are sufficient for diagnosis.